Weedy rice (Oryza sativa L.) problem in rice (Oryza sativa L.) based cropping systems in the Philippines. - Tanzo, Irene R.; Martin, Edwin C.; Chauhan, Bhagirath S. (Scientific Research Publishing, Inc., 2013)
A study was undertaken in February 2012 to understand the knowledge and practices of rice farmers about weedy rice in two municipalities of Iloilo, Philippines. The specific objectives of the study were to establish what rice farmers know about weedy rice, examine rice farmers’ practices in managing weedy rice, and recommend policies on weedy rice management based on the results of the study. Farmers’ knowledge of weedy rice did not differ much between two villages. Results showed that 41% from the second most affected village and 33% from the most affected village thought that weedy rice cannot reduce the market value of the harvested rice. Majority of the farmers (68%) responded that awns can be absent in some weedy rice and about 40% of the farmers did not know that seeds of weedy rice have dormancy. Cutting the weedy rice panicles at harvest, as the best way of reducing weedy rice, was practiced by majority of the respondents (82%) from the most affected village. Our study suggests that there is a need to increase awareness about weedy rice among Asian farmers.